Differential Diagnosis and Histopathological Analysis of Localized Gingival Overgrowths: Study of 218 Cases from Northeast Thailand - Morilla, Lordjie Marr; Subarnbhesaj, Ajiravudh; Klanrit, Poramaporn (Journal of Dentistry Indonesia, 2020)
Localized gingival overgrowths (LGOs) are relatively common clinical findings. These lesions can be associated with chronic irritation, infections, or they can represent benign or malignant tumors that can either be primary or metastatic. The etiology of these lesions is multifactorial, but the most prevalent cause is reactive hyperplasia and inflammation induced by dental plaque. Objective: This study presents the prevalence of LGOs in Northeast Thailand and identifies the most common LGOs in the region. Methods: A series of 218 LGO cases was studied. Results: Pyogenic granuloma (PG), gingival squamous cell carcinoma (GSCC), and peripheral ossifying fibroma (POF) were the three most common LGOs in this study. There were also interesting cases of soft tissue counterparts of benign odontogenic tumors and metastatic carcinomas to the gingiva with no evidence of bone invasion observed. Conclusion: The three most common LGOs in Northeast Thailand were PG, GSCC, and POF. This study provides baseline data on the prevalence of LGOs in Northeast Thailand.